Characterization of the content of microelements in the soil-plant-animal system and its influence on cattle reproduction in the central region of Cuba - Garc?a, juan Ram?n; Cuesta, M.; Garc?a L?pez, Roberto; Qui?ones, R.; Figueredo, J. M.; Faure, R.; Pedroso, R.; Mollineda, A. (Cuban Journal of Agricultural Science, 2010)
The objective of this study was to assess the content of microelements in soil, pastures, dairy cows, and reproductive indicators in herds of the central southern area of the Villa Clara province. Four herds were used representing this area, two cattle units and two heifer rearing centers. The characteristics of the mineral composition of the soil, the pasture, and the mineral profile of the animals including reserve organs and the reproductive indicators were studied. The descriptive statistics were calculated for all the variables, the levels of microelements in the pasture in the two seasons, and between cows and heifers. In the soil, 61, 66, 77, and 100 % of the samples were found to be deficient in Fe, Mn, Zn, and Cu, respectively. In the pasture, during the rainy season, there were deficiencies of Mn, Zn, and Cu in 38, 33, and 100 %, and, during the dry season, Mn and Cu were deficient in 27 and 100 % of the samples. The 75 % of the samples of blood serum were deficient in Cu and in hepatic tissue. The 72, 42, and 50 % of the samples were diagnosed as deficient in Cu, Zn, and Mn, respectively. It is concluded that in the area under study the most acute mineral deficiency was that of Cu, also diagnosing deficiencies of Zn and Mn, and a marked deterioration of the reproductive indicators. Key words: reproductive indicators, mineral composition, deficiencies, cattle, milk.